2022
DOI: 10.1155/2022/4047845
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Augmented Reality for Lower Limb Rehabilitation: A Systematic Review

Abstract: Augmented reality- (AR-) based interventions have shown potential benefits for lower limb rehabilitation. However, current literature has not revealed these benefits as a whole. The main purposes of this systematic review were to determine the efficacy of AR-based interventions on lower limb recovery of the larger population based on the current process that has been made in this regard. Relevant studies were retrieved from five electronic databases (Web of Science, PubMed, ScienceDirect, Scopus, and Cochrane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…They suggested that patients getting VR and AR treatment for hand rehabilitation can be improved over conventional therapy. A systematic review in Reference 26 included studies on using AR for lower limb rehabilitation for elderly adults, stroke patients, and Parkinson's patients. It initially proved the notable benefits of AR‐based therapies on lower limb rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that patients getting VR and AR treatment for hand rehabilitation can be improved over conventional therapy. A systematic review in Reference 26 included studies on using AR for lower limb rehabilitation for elderly adults, stroke patients, and Parkinson's patients. It initially proved the notable benefits of AR‐based therapies on lower limb rehabilitation.…”
Section: Introductionmentioning
confidence: 99%